TEACHING ENGLISH VOCABULARY TO THE FIFTH YEAR STUDENT AT SD N 3 DONOHUDAN BOYOLALI IN 2009/2010 ACADEMIC YEAR - LESTARI, DEWI PUJI (2010)
This research paper aims at describing the methods teaching learning vocabulary at elementary school of SDN 3 Donohudan Boyolali, and describing problems faced by the teacher and the students in teaching learning English vocabulary at SDN 3 Donohudan Boyolali. This research is a descriptive qualitative research. The subject of the research is the English teacher, the object of the research is the process of teaching, and learning vocabulary of the student at SDN Donohudan Boyolali.The researcher collects the data by observing the English class and conducting in interview with the teacher and the students. The data include the vocabulary materials, field notes and interview script. While the methods of collecting of the data are observation, interview, and documents. The result of the research show that the first, the methods used by the teacher in teaching vocabulary at the fifth year students of SDN 3 Donohudan Boyolali is Grammar Translation Method (GTM). The second, objective of the study is to fulfill demand of globalization and increasing the student‟s competences. The thirds, the problems faced by the teacher are; a. the teacher finds difficulties in managing the students in the class, b. the students have low motivation, c. each student has different capability in receiving the material, and d. the teacher has limited time. and the last, the problems faced by the students in learning vocabulary are; not all students like studying English, translating the text, reading the words and writing the words.